The Influence of the Blue Economy on National Economic Growth - Mariyatul Qibtiyana; Istianingsih Sastrodiharjo; Yayan Hendayana (Greenation International Journal of Economics and Accounting, 2024)
Economic growth is the main focus of the country's development, especially measured through Gross Domestic Product (GDP). In the Indonesian context, the blue economy concept is a promising strategy because of the abundant potential of marine resources. This study aims to analyze the influence of the blue economy on economic growth in Indonesia. Through a literature review, it is revealed that the government has implemented various innovative policies and financial instruments to support the blue economy. The research results show that the blue economy has a significant influence on economic growth. However, the challenge of maximizing the benefits of marine resources while maintaining environmental sustainability remains the main focus. By maintaining the sustainability of marine resources, Indonesia can build a strong and sustainable blue economy, providing long-term economic and social benefits for its people.